Case report: Diagnosis of a patient with Sifrim–Hitz–Weiss syndrome, development and epileptic encephalopathy-14, and medium chain acyl-CoA dehydrogenase deficiency - Zeka, Naim; Zeka, Eris; Zhubi, Esra; Hoxha, Ilir (Frontiers in Pediatrics, 2023)
Background: It is generally recognized that genetic metabolic disorders can result in neurological symptoms such as seizures, developmental delay, and intellectual disability. Heterogeneous clinical presentations make the diagnosis challenging.In this case report, we present a unique and complex genetic disorder observed in a female patient who exhibited three pathogenic gene variants in the KCNT1, ACADM, and CHD4 genes. The convergence of these variants resulted in a multifaceted clinical presentation characterized by severe seizures of combined focal and generalized onset, metabolic dysfunction, and neurodevelopmental abnormalities. The identification and functional characterization of these gene variants shed light on the intricate interplay between these genes and their impact on the patient's phenotype. EEG revealed an epileptiform abnormality which presented in the inter-ictal period from the left frontal-central area and in the ictal period from the left mid-temporal area. The brain MRI revealed volume loss in the posterior periventricular area and parietal parenchyma, myelin destruction with no sign of hypoxic involvement, and left dominant enlargement of the lateral ventricles secondary to loss of central parenchyma. She was diagnosed through exome sequencing with Sifrim-Hitz-Weiss syndrome, development and epileptic encephalopathy-14, and medium-chain Acyl-CoA dehydrogenase deficiency. An antiseizure medication regimen with valproic acid, levetiracetam, phenobarbital, and clonazepam was initiated. However, this led to only partial control of the seizures.Clinical follow-up of the patient will further define the clinical spectrum of KCNT1, ACADM, and CHD4 gene variants. It will also determine the long-term efficacy of the treatment of seizures and the development of precision medicine for epilepsy syndromes due to gain-of-function variants. Special emphasis should be put on the role and importance of large-scale genomic testing in understanding and diagnosing complex phenotypes and atypical epileptic syndromes.